Peningkatan Ekonomi Desa melalui Pariwisata: Memahami Regulasi dan Manfaatnya - Hurriati, Laili; Fitriatun Nisa, Puza; Yuni Putri, Iin; Rifais, Muh; Fatiha, Fatun (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Aik Bukaq Village possesses significant tourism potential, but it has not been fully leveraged to stimulate the local economy. This community service program aims to enhance the understanding of the Aik Bukaq Village community regarding tourism regulations and the benefits that can be derived from developing this sector. A thorough understanding of regulations, such as licensing, environmental conservation, and natural resource management, is crucial for ensuring that tourism development proceeds sustainably and generates positive economic impacts. The program also involves training and mentoring the community to optimize existing tourism potential, including local product development, marketing strategies, and tourism management. The expected outcome includes increased community knowledge of tourism regulations and improved economic income through better-managed tourism. Consequently, this program is anticipated to contribute to strengthening the economy of Aik Bukaq Village and improving the overall well-being of the community